Konsep Kebebasan Menurut Will Kymlicka - Solilit, Fidelis (Fakultas Teologi, Universitas Sanata Dharma, 2024)
This article talks about Will Kymlicka's concept of freedom. It should be noted that the emergence of Kymlicka's idea of freedom is inseparable from his big theme of